Maximum Ride : the manga. 4 - Lee, NaRae; Patterson, James, 1947-; Patterson, James, 1947- (London : Arrow Books, 2011)
The Flock members try to live normal lives by going to school and making friends while they search for their parents, but when the Erasers return the group must escape again and Max finds that her destiny is to save the world.
Based on: Maximum ride / James Patterson.
Young Adult.
Young Adult
Keywords: Patterson, James, -- 1947- -- Adaptations -- Juvenile literature; Patterson, James, -- 1947- -- Adaptations; Patterson, James, -- 1947- -- Adaptations; Genetic engineering -- Comic books, strips, etc -- Juvenile fiction; Good and evil -- Comic books, strips, etc -- Juvenile fiction; Scientists -- Comic books, strips, etc -- Juvenile fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Genetic engineering -- Fiction; Good and evil -- Fiction; Science fiction; Scientists -- Fiction; Adventure graphic novels; Comic books, strips, etc; Genetic engineering -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Graphic novels; Manga; Science fiction graphic novels; Scientists -- Comic books, strips, etc -- Fiction; Adventure fiction; Graphic novels; Science fiction comic books, strips, etc